Swift heavy ion irradiation puts InGaN/GaN multi-quantum wells on the track for efficient green light emission - M. Sall; G. Sow; A. Baillard; A. Dujarrier; L. Goodwin; J.G. Mattei; M. Sequeira; M. Peres; P. Loiko; Y. Doublet; M.P. Chauvat; C.A.P. da Costa; et al. (Nano Trends)
InN and InGaN/GaN multi-quantum wells (MQWs) were subjected to Swift Heavy Ion (SHI) irradiation. Ion track formation was studied using transmission electron microscopy in both plane view and cross-sectional modes. InN shows a remarkable sensitivity towards track formation with a material decomposition experimentally evidenced by means of Electron Energy Loss Spectroscopy. The MQWs material shows higher stability with negligible GaN/InGaN interface intermixing along the SHI tracks. This intermixing, proposed for mitigating polarization effects in InGaN/GaN-based light emitting diodes (LED), was achieved by track-free SHI irradiation. This was combined with low temperature thermal treatment at 450 °C with the aim to both create a compositional gradient at the MQWs interfaces and preserving the material luminescence. The obtained results pave the way for the use of SHI irradiation for efficient green light emission of InGaN/GaN-based LED.